2008
DOI: 10.1080/09638180701819865
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in Fair Value Accounting: UK Investment Vehicles

Abstract: Acknowledgements:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 39 publications
(28 reference statements)
4
40
0
2
Order By: Relevance
“…Fair value estimates, especially for Level 3 assets, are heavily reliant on valuation estimation models and assumptions, which may result in unintentional or intentional bias. For example, Benston (, p. 106) claims that ‘dishonest and opportunistic CFOs and CEOs are likely to find fair value accounting a boon to their efforts to manipulate reported net income.’ Several empirical studies have evidenced deliberate managerial bias in fair value accounting (Dietrich et al ., ; Hodder et al ., ; Danbolt and Rees, ; Ramanna, ). In addition, previous studies have supported the argument that assessing fair market value involves subjectivity.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Fair value estimates, especially for Level 3 assets, are heavily reliant on valuation estimation models and assumptions, which may result in unintentional or intentional bias. For example, Benston (, p. 106) claims that ‘dishonest and opportunistic CFOs and CEOs are likely to find fair value accounting a boon to their efforts to manipulate reported net income.’ Several empirical studies have evidenced deliberate managerial bias in fair value accounting (Dietrich et al ., ; Hodder et al ., ; Danbolt and Rees, ; Ramanna, ). In addition, previous studies have supported the argument that assessing fair market value involves subjectivity.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Plantin, Sapra, and Shin [2008] present an analytical model that compares conditions (specifically, short‐lived/long‐lived assets, liquid/illiquid assets, and junior/senior assets) under which historical cost measurement systems result in lower inefficiencies than fair value accounting measurement systems. Similarly, archival studies also compare the value relevance of historical cost accounting versus fair value accounting (e.g., Danbolt and Rees [2008], Christensen and Nikolaev [2010]). However, prior research provides little empirical evidence on the effect of fair value versus historical cost accounting on managerial decisions 7…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As noted previously, in general, prior studies have shown that the information obtained by applying FVA is more relevant for users than that derived from the historical cost approach, but also less reliable (Betts and Wines, 2004; Elad, 2004; Häusler, 2004; Bies, 2005; Ball, 2006). Using FV could produce greater bias in the financial information reported (Ronen, 2008; Danbolt and Rees, 2008). The lower degree of reliability with FVA, in comparison to historical cost, is usually associated with difficulties in obtaining market prices to quantify asset values (AAAFASC, 2005).…”
Section: Fair Value As a Means Of Improving Government Financial Statmentioning
confidence: 99%